CARACTERISTICILE PROCESULUI DE ADAPTARE PSIHOSOCIALĂ A STUDENŢILOR LA MEDIUL UNIVERSITAR - USM ADMIN (Moldova State University, 2008)
In case from adjustment of student interest modification in stokes show from personality, as inside, alike environment relations. After claster analysis for determined similarity and difference of personality specific feature was proved the existence of traditional combination by first present's factors in case of clasters. From here we inferring that general characteristic are determined non from sum from specific feature whom they embodiments, but from system from relations what exist among they.